Photoactivation: The Light-Driven Assembly of the Water Oxidation Complex of Photosystem II - Bao, Han; Burnap, Robert L. (Frontiers in Plant Science, 2016)
Photosynthetic water oxidation is catalyzed by the Mn4CaO5 cluster of photosystem II. The assembly of the Mn4O5Ca requires light and involves a sequential process called photoactivation. This process harnesses the charge-separation of the photochemical reaction center and the coordination environment provided by the amino acid side chains of the protein to oxidize and organize the incoming manganese ions to form the oxo-bridged metal cluster capable of H2O-oxidation. Although most aspects of this assembly process remain poorly understood, recent advances in the elucidation of the crystal structure of the fully assembled cyanobacterial PSII complex help in the interpretation of the rich history of experiments designed to understand this process. Moreover, recent insights on the structure and stability of the constituent ions of the Mn4CaO5 cluster may guide future experiments. Here we consider the literature and give a possible model of assembly involving single Mn2+ oxidation site and ion relocation.